Minutes of the Thirty-first Regular Meeting Rocky Mountain Coal Mining Institute held at Salt Lake City, Utah June 22nd, 23rd and 24th, 1932 (Rocky Mountain Coal Mining Institute, 1932)
The thirty-first regular meeting of the Rocky Mountain Coal Mining Institute was called to order at 11: 10 o'clock A. M., Wednesday, June 22nd, 1932, President T. H. Butler presiding. The Honorable Louis Marcus, Mayor of Salt Lake City, delivered the address of welcome. On motion of W. H. Bachman and seconded by D. J. Parker, it was voted that, inasmuch as the Minutes are printed in the annual bulletin, the reading of them be dispensed with. The President made his annual report. The Secretary-Treasurer made his annual report of the financial condition of the Institute. R. Dawson Hall addressed the meeting. The following committees were appointed by the President: Auditing-L. P. Pearce, Chairman; Joseph, Parmley, R. R. Knill. Nominating John Emrick, Chairman; D. J. Parker, John Marks. Resolutions-D. R. Wilson, Chairman; H. Petersen, Robert Williams, Jr. There being no further business to come before the meeting, the same was adjourned at 11: 55 o'clock A. M.